FAKTOR-FAKTOR FUNDAMENTAL MIKRO: PERTUMBUHAN AKTIVA, PERTUMBUHAN TINGKAT PENGEMBALIAN AKTIVA, RASIO UTANG, RASIO LANCAR, LABA BERSIH PER SAHAM, RASIO HARGA-LABA BERSIH PER SAHAM & HASIL (PENDAPATAN) SAHAM YANG BERPENGARUH TERHADAP HARGA SAHAM INDUSTRI MAKANAN & MINUMAN PADA BURSA EFEK DI INDONESIA - Bambang Hadi Santsoso (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
The population of this research is shares of the issuers (go public companies) in the food and beverage industry listed on the stock exchange in Indonesia. The research period is 4 years (from year 1998 to2001), and its sample consists of 10 shares of issuers in the industry of food and beverage. The sample was taken from 18 shares of issuers, with the implementation of purposive or non-random sampling technique. The capital market roles are so important, and therefore, ideally, the analysis with the focus on factors and on dominant factors influenced price of shares is really needed to be carried out through a detail research. Focus of this research is on the impact of micro fundamental factors towards price of shares of the food and beverage industry listed on the stock exchange in Indonesia, especially after economy and monetary crisis happened in 1997 in Indonesia. Variables studied in the research are price of shares, and asset growth, return on asset growth, debt ratio, current ratio, earning per share, price earning ratio, and also dividend yield. The source of data is secondary data obtained from the Surabaya and Jakarta Stock Exchanges, as well as Capital Market Reference Center. The model used for this research is multiple linier regressionanalysis model. Result of research concluded that the changes on price of shares of the food and beverage industry listed on the stock exchange in Indonesia were influenced simultaneously by asset growth, return on asset growth, debt ratio, current ratio, earning per share, price earning ratio, and dividend yield. Meanwhile, the changes on price of shares of the food and beverage industry listed on the stock exchange in Indonesia was influenced partially by only earning per share.